Da elaboração de um artigo multimídia - AMM à formação de uma comunidade de aprendizagem: um olhar para o desenvolvimento profissional - Costa, Tânia Margarida Lima (2008)
The present research aims to investigate the professional development of a Math teachers group in a process of building a videopaper. Videopapers are multimedia documents that include a text frame, a comment frame, a video frame and an image frame, contents of which are interrelated in multiple ways. In order to start the discussion among the teachers, we have selected a problem in which they were supposed to represent a person s movement in the graphic. First, they used paper and pencil and, then, a TI Graphing Calculator. When they were building the videopaper, the teachers began selecting images and excerpts of speeches from videotaped episodes of their actions in the proposed activities. Right after that, they had access to a videopaper and initiated the process of structuring the one that was going to be built by the group. During this process, the teachers constituted a group, which, in the perspective of Wenger (2001) is a Community of Practice. We have chosen as reference theories that connect Teacher s Professional Knowledge, Movement Math and Discourse Interactions. This research analyzed the teachers discourses in the light of Modelo da Estratégia Argumentativa (CASTRO e FRANT, 2000) and of Tipologia do Discurso (NEMIROVSKY, 2005). From this perspective, we made an attempt to comprehend better the relationships between the production of narratives about the practice and the development of the professional knowledge. The research methodology is in the field of qualitative investigation, in which we have adopted Design Experiments in Educational Research (COBB et al., 2003) as a guide. To conclude, the research results showed that the opportunity to watch classroom episodes repeatedly was important for the teachers. They could not only think about their own mathematical knowlege, but also reflect on their own classes, by analyzing the different manners in which their students express themselves and how they would do that using technology. We also observed that the discourse changed after the video. It turned out more grounded into the images, which gave the opportunity to arise a judgment discourse about other classes that have not been recorded. Finally, this research showed how Communities of Professional Knowledge composed by a researcher and teachers can be excellent opportunities to master the professional development of the grou